2020
DOI: 10.3390/ph13100269
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical Constituents and Pharmacological Activities of Annona atemoya: A Systematic Review

Abstract: Annona atemoya also known as the custard apple is a hybrid between two Annonaceae species: Cherimoya (Annona cherimola) and the sugar apple (Annona squamosa). It is widely cultivated in tropical and subtropical continents including north and south America, Asia, Africa and Australia. Despite becoming an increasingly important commercial fruit plant due to its’ creamy succulent flesh, compared to other Annonaceae species relatively few studies have investigated the phytochemistry and bioactivities of A. atemoya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This effect was caused by the action of the epidermal growth factor receptor/G protein-coupled receptor kinase 2 pathway. These activities were even higher than other extracts from previously characterized medicinal plants (Kazman et al, 2020). These data showed that the extract of species of the family Annonaceae may be the basis of future drug development for neurological disorder treatment.…”
Section: Therapeutic Against Neurological Disordersmentioning
confidence: 61%
See 1 more Smart Citation
“…This effect was caused by the action of the epidermal growth factor receptor/G protein-coupled receptor kinase 2 pathway. These activities were even higher than other extracts from previously characterized medicinal plants (Kazman et al, 2020). These data showed that the extract of species of the family Annonaceae may be the basis of future drug development for neurological disorder treatment.…”
Section: Therapeutic Against Neurological Disordersmentioning
confidence: 61%
“…Experiments using antibody microarray analysis showed that epidermal growth factor receptor was induced in neuronal cells in mice. The technique of high-performance liquid chromatography showed that rutin is highly present in the extract of this Annona hybrid and together with isoquercitrin revealed inhibitory action on Aβ aggregation (Kazman et al, 2020). This evidence demonstrated that rutin is a bioactive compound against Alzheimer's disease.…”
Section: Therapeutic Against Neurological Disordersmentioning
confidence: 81%
“…The presence of acetogenin, alkaloids, essential oils, phenolic compounds, cyclic peptides, amino acids, dyes, and vitamins has also been reported from the extract of different Annona plant parts (Bhardwaj et al 2020). In addition, alkaloids and flavonoids are found in the seeds of A. atemoya and A. squamosa (Al Kazman et al 2020;Kumar et al 2021).…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Many tropical and subtropical continents, including southern and northern America, Asia, Africa, and Australia, as well as Spain, are home to A. atemoya cultivation. A. atemoya is a cross between the Cherimoya (Annona squamosa) (Li et al 2019; Kazman et al 2020). A. atemoya is short-branched with low, drooping branches and grows to a height of around 7.5 to 10 m. The leaves of A. atemoya, which average 15 cm in length, are alternate, leathery, deciduous, and less hairy than those of the parent cheimola.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation